Two Paratylenchus species (Nemata: Tylenchulidae) from Martinique and New Caledonia (Journal of Nematode Morphology and Systematics, 2010)
Paratylenchus macrodorus Brzeski, 1963 and P. salubris Raski, 1975 are described and figured from New Caledonia and Martinique, respectively. Scanning electron microscope photographs are presented for the first time. These two relatively scarce species are discussed and compared with the descriptions and other information on them given by previous authors